CD47 and TREM2 for macrophage-targeted cancer immunotherapy: Antibody validation and ex vivo efficacy in patient-derived explant cultures - Westerholm, Satu (My University, 2024)
Cancer remains a common cause of death worldwide. Cancer cells develop several mechanisms to escape immune destruction, which limits the efficacy of current treatments and creates a need for new therapies. Cancer immunotherapies aim to re-activate the immune system against cancer. Targeting tumor-associated macrophages (TAMs) has been considered a promising strategy as macrophages play important roles in both cancer immune evasion and growth promotion. The aim of this study was to first validate the function of in-house produced TAM-targeting cancer immunotherapeutics, anti-CD47 and anti-TREM2 antibodies, and then compare their efficacy in ex vivo treated breast cancer explants. To validate anti-CD47, the proportion of macrophages that had phagocytosed T47D cancer cells was measured with flow cytometry. To validate anti-TREM2, HEK-EBNA cells transfected with TREM2 or TREM2-expressing macrophages were quantified for TREM2 expression with flow cytometry and treated with anti-TREM2. The ability of anti-TREM2 to induce antibody-dependent cellular cytotoxicity (ADCC) was measured using Jurkat-Lucia™ NFAT-CD16 cells. Anti-CD47 and anti-TREM2 were compared by treating 12 breast cancer patient tumors ex vivo and analyzing 23 cytokines from the culture supernatants. As expected, anti-CD47 increased macrophage-mediated cancer cell phagocytosis. Treating TREM2-expressing cells with anti-TREM2 induced a modest induction in ADCC in comparison to TREM2-/low control cells and IgG4. These results are in line with the known modes-of-action of these antibodies. In ex vivo treated breast cancer tumors, anti-CD47 induced stronger overall and pro-inflammatory cytokine and chemokine secretion than anti-TREM2.
Keywords: cancer immunotherapy, tumor-associated macrophages, antibody, cytokine